Social Cognitive Career Theory Pada Minat Berwirausaha Siswa SMK - Yan Fitri, Mellyna Eka; Hastini, Lasti Yossi; Chairoel, Lucy (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2024)
Entrepreneurship contributes to a country's economy because it can open up employment opportunities. Vocational schools are one of the important places in producing entrepreneurs. Several previous research results show the low interest in entrepreneurship among vocational school students, and it even appears that entrepreneurship is not an option for them after graduating. This research aims to examine the influence of entrepreneurial knowledge, entrepreneurial self-efficacy and entrepreneurial outcome expectations on entrepreneurial interest. This research was carried out using quantitative methods. The research was conducted at SMK N 8 Padang with 157 students as respondents. By using SEM-PLS, the research results show that there is a positive and significant influence of entrepreneurial self-efficacy on entrepreneurial outcome expectations. Entrepreneurial outcome expectations do not mediate the relationship between entrepreneurial self-efficacy and entrepreneurial interest. Abstrak Entrepreneurship atau kewirausahaan berkontribusi pada perekonomian suatu negara karena dapat membuka lapangan kerja. SMK merupakan salah satu tempat yang penting dalam menghasilkan wirausahawan. Beberapa hasil penelitian terdahulu memperlihatkan rendahnya minat berwirausaha yang dimiliki oleh murid-murid SMK, bahkan terlihat bahwa berwirausaha bukan menjadi pilihan mereka setelah lulus. Penelitian ini bertujuan untuk menguji pengaruh entrepreneurial knowledge, entrepreneurial self efficacy dan entrepreneurial outcome expectation terhadap entrepreneurial interest. Untuk mencapai tujuan tersebut, penelitian dilakukan dengan metode kuantitatif. Penelitian dilakukan di SMK N 8 Padang dengan responden sebanyak 157 siswa. Dengan menggunakan SEM-PLS, hasil penelitian menunjukkan bahwa terdapat pengaruh positif dan signifikan entrepreneurial self efficacy terhadap entrepreneurial outcome expectation. Entrepreneurial outcome expectation tidak memediasi hubungan antara entrepreneurial self efficacy dan entrepreneurial interest.